The Shipwreck of the Airship “Dirigibile Italia” in the 1928 Polar Venture: A Retrospective Analysis of the Ionospheric and Geomagnetic Conditions - B. Zolesi; M. Pezzopane; C. Bianchi; A. Meloni; Lj. R. Cander; R. Tozzi (Space Weather)
Abstract On 25 May 1928 the airship “Dirigibile Italia” during its return trip to the base in NyAlesund, after overflying the North Pole, shipwrecked on the ice‐pack in a region at about 400 km northeast of Svalbard Islands. Survivors, by using a portable high frequency (HF) radio transmitter, tried unsuccessfully to send SOS messages and to establish a radio link with the ship “Città di Milano” of the Italian Navy, closely anchored at King's Bay. Only after 9 days of repeated radio‐distress transmissions, a Russian radio amateur close to the town of Arkhangelsk about 1,900 km away was able to receive the messages launched by the survivors and raise the alarm. This paper aims at giving a retrospective analysis of the ionospheric and geomagnetic conditions of that epoch in order to explain the HF radio communications problems encountered by the survivors. The International Reference Ionosphere model has been applied, and early geomagnetic measurements have been evaluated, to come up with theories explaining the events. We assert the HF transmission difficulties were associated with the “radio silent” or “dead zones” associated with F‐region propagation. These may have been exacerbated by solar and geomagnetically disturbed conditions of the days immediately following the airship wreck.